Suddenly - Sinatra, Frank, 1915-1998; Sale, Richard, 1911-1993 (Libra Productions, Inc., 1954)
Three hired gunmen set themselves up to assassinate the President in Suddenly, a California town, where he is secretly scheduled to transfer from a special train to a car. They seize a strategic location in a private residence, and proceed to terrorize the occupants.